Rancang Bangun Alat Uji Kapasitas Baterai Lithium-Ion Berbasis Arduino Mega - Waruwu, Riani; Mohd. Ilyas Hadikusuma; Rianda (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2025)
Lithium ion 18650 capacity batteries suffer from various issues that affect the performance and lifespan of the battery. One of the main issues is capacity degradation over time and use, which reduces the duration of device use and forces users to frequently replace or charge the battery. In addition, overcharging and overdischarging can damage battery cells, shorten battery life, and create unsafe conditions. Battery capacity that does not match the information on the label is also often a problem, which harms consumers and reduces device performance due to the poor performance of the battery. Therefore, it is necessary to make a tool that can test the battery capacity to anticipate this happening. With the Design of an Arduino Mega-based Lithium-ion Battery Capacity Test Tool used to determine battery performance when connected in series and connected in parallel without having to check the battery capacity one by one. With the creation of this tool, it is hoped that it can help users to find out the condition of the battery that is still prime or not and the user can find out the condition of the battery capacity is still a lot or not.